Isolasi Dan Karakterisasi Bakteri Dari Tanah Pada Lahan Praktek Mahasiswa Fakultas Biologi Universitas Medan Area - Saputri Handayani (Universitas Medan Area, 2022)
Soil is a habitat for various microorganisms such as bacteria and fungi that affect soil fertility. Research on the isolation and characterization of bacteria from the soil on students' practice fields at the Faculty of Biology, University of Medan Area was carried out. The purpose of this study was to determine the characteristics of bacteria found in the soil on the practice land of the Faculty of Biology students of the Medan Area University. There are three stages in the study, namely isolation, characterization and data analysis. From the results of data analysis obtained two types of bacterial isolates with different characteristics, namely sp1 and sp2. Sp1 isolates are gram negative bacteria in the form of bacilli cells, sp2 isolates are gram negative bacteria in the form of bacilli cells. Sp1 and sp2 isolates are known to be able to ferment sugars and citrates in biochemical test reactions.